GENOTYPIC AND PHENOTYPIC CORRELATION IN MAIZE AND PATH COEFFICIENT I- Agronomic Traits - & et al., K.M.Wuhaib (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
To estimate the genetic parameters and path coefficient of plant traits that correlate with yield to rely on them as selection criteria for maize breeding. Seeds of four genotypes selected from cv. Buhoth were planted at the field of Field Crop Dept. College of Agriculture Univ. of Baghdad during spring and fall season 2013, under two levels of nitrogen fertilizer (200 and 400kgN.ha-1.). Data were analyzed, and genotypic and phenotypic correlation and path coefficient were estimated. The results revealed that these traits contributed 44% and 48% of yield variance at spring under 200 and 400 kg N.ha-1, and 56% and 73% of yield variance at fall season, under 200,400 kg N.ha-1 respectively.The results showed that the studied traits, plant height and ear height, number of ears (spring) and number of leaves, leaf area and number of ears (fall) under 200 kg N.ha-1., exhibited positive and highly significant genetic and phenotypic correlations; days to tasseling, number of leaves, and leaf area (spring), number of leaves and number of ears at fall, under 400 kg N.ha-1. At 200 kg N.ha-1, days to silking and number of leaves(spring), ear height and number of leaves (fall); days to tasseling , leaves area, and ears height (spring); plant height and number of ears (fall) under 400 kg N.ha-1 had the highest positive direct effect on grain yield. It can be conclude that number of ears and number of leaves can be use as selection criteria in breeding and improvement programs of yield in maize.